PENINGKATAN LITERASI BAGI APARATUR LAYANAN PUBLIK MELALUI EDUKASI TEKNOLOGI BLOCKCHAIN DALAM MENDUKUNG LAYANAN E-GOVERNMENT DI SAMSAT KUNINGAN - Azizah Zakiah; Viddi Mardiansyah; Ulil Surtia Zulpratita; Yenie Syukriyah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
Digital transformation in public services requires the enhancement of technological literacy among government officials, particularly regarding blockchain technology which has the potential to improve transparency, data security, and efficiency in e-Government services. However, the level of understanding of this technology among public service officers remains relatively low. This Community Service Program (PKM) aims to improve blockchain technology literacy among public service officers at the Regional Revenue Management Center of Kuningan Regency as part of efforts to support e-Government development. The activity was conducted through a webinar-based socialization and educational program consisting of material presentations, interactive discussions, and evaluation of participants’ understanding using pre-test and post-test instruments. The results indicate a significant improvement in participants’ understanding, where most participants who were initially in the low understanding category shifted to the good understanding category after the activity. This improvement is also reflected in the Understanding Index (UI) and the percentage of learning achievement increase. Furthermore, high participant enthusiasm and active involvement during the activity demonstrate the effectiveness of the program. This PKM activity provides a meaningful contribution to strengthening the readiness of human resources as an initial foundation for implementing blockchain technology to support more transparent, secure, and efficient e-Government services.